2012
DOI: 10.1097/bsd.0b013e31825010ae
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying Loupes Versus Microscope for Microdiscectomy and Microdecompression

Abstract: Microscopes are better than loupes as they provide a much better visualization, are more comfortable for the surgeon, and are a much better teaching tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A 2012 study by Kumar et al compared loupes to microscope use for microdiscectomy and microdecompression in 102 patients, and found that microscopes were associated with an increased average operative time of 4 minutes. 10 Older studies that compared microscope cases to non-microscope cases have similarly found increased average operating room times with microscope use, ranging from 5 minutes to 29 minutes. 7-9 However, these previous studies were generally small, single-institution case series with differing surgical techniques, making it difficult to compare results among them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2012 study by Kumar et al compared loupes to microscope use for microdiscectomy and microdecompression in 102 patients, and found that microscopes were associated with an increased average operative time of 4 minutes. 10 Older studies that compared microscope cases to non-microscope cases have similarly found increased average operating room times with microscope use, ranging from 5 minutes to 29 minutes. 7-9 However, these previous studies were generally small, single-institution case series with differing surgical techniques, making it difficult to compare results among them.…”
Section: Discussionmentioning
confidence: 99%
“…These results are additionally supported by similar findings in the above-mentioned studies that found no difference in the rates of postoperative infection between non-microscope and microscope groups. 3,5,7,10 However, due to the low patient numbers and the relatively rare incidence of postoperative infection, these earlier studies may not have been adequately powered to detect differences in infection rates between groups. For example, Kumar et al reported one postoperative infection in the non-microscope group and zero infections in the microscope group, concluding that the infection rate was similar between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation